The deformation and processing of structural materials - Guo, Z. Xiao (Woodhead Publishing in materials., 2005)
Having a good understanding of a construction material's performance under different conditions is essential for helping engineers in selecting the right type of material for a job and for setting design specifications. Keeping abreast of the latest research is an important part of this. The deformation and processing of structural materials is divided into eight chapters, each one exploring a material's processing and deformation behaviour. They also consider how the microstructural composition of materials is affected by processing and what influence this has on its subsequent in situ performance. The materials and behaviours looked at in the chapters include: aluminium and its alloys; magnesium alloys; ferrous alloys; superalloys (Ni-based alloys); semisolid metal (SSM) processing of metallic alloys; plastic deformation of intermetallic alloys; metal matrix composites (MMCs); and fine grain superplasticity in SP materials. The first of its kind to give comprehensive coverage to the subject, The deformation and processing of structural materials is a valuable resource for engineers, researchers in mechanical, civil and structural engineering. Contains research on the preformance of materialsValuable resource for researchers in mechanical, civil and structural engineeringComprehensive coverage to the deformation and processing of all types of structural materials.